Process Management in Organizations Exemplified by Cruise Shipping Companies - Joanna KIZIELEWICZ (Communications of International Proceedings, 2021)
Cruise ships are a certain type of floating cities of entertainment. Ship owners invest in various facilities for travellers and ensure that aboard their ships the highest quality sophisticated needs are satisfied. Cruise ships are also workplaces for many crew members and on board personnel, where various processes occur and need to be managed skilfully. Travellers perceive cruise ships as a place where luxurious services are rendered, and do not realize how many people work there to achieve the intended result. This study aims to identify the processes within the workflow aboard cruise ships. The conducted analysis may constitute interesting cognitive material for cruise ship future employees and cruise ship employee recruitment agencies, but it also constitutes reference material for cruise management.
Keywords: Process Management; Cruise Shipping Companies; Crusing.